2016
DOI: 10.1007/s40974-016-0028-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening of bacterial strains for developing effective pesticide-tolerant plant growth-promoting microbial consortia from rhizosphere soils of vegetable fields of eastern Uttar Pradesh, India

Abstract: The current study was intended to isolate and characterize the plant growth-promoting properties and pesticide (chlorpyripfos) tolerance ability of microbial strains for sustainable vegetable productions. Plant growthpromoting microorganism is a group of microbial consortia to improve crop growth and yield by various direct mechanisms, e.g. nitrogen fixation, phosphate solubilization, production of plant growth hormones, ammonia and siderophore, and indirect mechanisms, e.g. production of antibiotic, hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…For instance, under fungicide free environment, strain RP1 released 80.5 AE 2.5 mg mL À1 of IAA which declined regularly with consistent increase in kitazin concentration but a maximum reduction in IAA synthesis was recorded at 3Â (15.6 AE 0.5 mg IAA mL À1 ). In line with these ndings, Verma et al 42 have also reported similar secretion of IAA by various rhizosphere microbes. The production of IAA even at higher fungicide concentration indeed is a fascinating and encouraging property of soil microbiota, because such fungicide tolerant microbes when applied under fungicide contaminated soil are most likely to continue secreting IAA and making this essential growth enhancing phytohormone available to plants even under fungicide polluted soils.…”
Section: Phytohormone Cyanogenic Compounds and Nh 3 Production Undersupporting
confidence: 63%
“…For instance, under fungicide free environment, strain RP1 released 80.5 AE 2.5 mg mL À1 of IAA which declined regularly with consistent increase in kitazin concentration but a maximum reduction in IAA synthesis was recorded at 3Â (15.6 AE 0.5 mg IAA mL À1 ). In line with these ndings, Verma et al 42 have also reported similar secretion of IAA by various rhizosphere microbes. The production of IAA even at higher fungicide concentration indeed is a fascinating and encouraging property of soil microbiota, because such fungicide tolerant microbes when applied under fungicide contaminated soil are most likely to continue secreting IAA and making this essential growth enhancing phytohormone available to plants even under fungicide polluted soils.…”
Section: Phytohormone Cyanogenic Compounds and Nh 3 Production Undersupporting
confidence: 63%
“…Improved nutrient acquisition in T13 (tetra-inoculant) and then T11 and T12 (tri-inoculant) treatments was due to increased nutrient uptake of N from nitrogen-fixing bacteria, uptake of P from phosphate mineral solubilizing bacteriaand uptake of iron from siderophore producing bacteria (Pseudomoas putida and Trichoderma sp.) and suppressing plant diseases (Verma et al, 2016;Jaiswal et al, 2019). It was also reported by Sani et al (2020) that Trichoderma sp.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme activity such as oxidase, catalase, urease, triple sugar iron agar test, citrate test, indole, MR-VP test [38,39], and motility test were carried out according to method of Litchfield and Gillevet [40].…”
Section: Bacterial Strain Isolation and Purificationmentioning
confidence: 99%